Fresh Produce Retail Price Comparisons in Trinidad and Tobago - Iton, C. W. Ardon; Seepersad, Govind (Applied Studies in Agribusiness and Commerce, 2018)
As the competitive landscape of the food and grocery retailing sector in Trinidad and Tobago is being transformed and consumers are separated from producers, shoppers are more reliant on price/quality cues in making their purchase decisions. The purpose of this study is to identify the retail outlet with the lowest and or highest price for a selected number of fresh produce items, in an effort to direct shoppers to relatively cheap nutritious sources of fresh produce. ANOVA and the Games-Howell test were the analytical procedures used. The ANOVA results indicated that there is statistical difference for all the items at the different retail outlets – farmers’ markets, roadside markets, public markets and supermarkets.The Games-Howell results obtained indicated that the supermarket mean prices were the highest for all items. Shoppers who purchased pineapple at the farmer’s market instead of the supermarket in 2016 could have potentially achieved the greatest savings of $6.52/kg.JEL Classification: C12, Q13, M31